2021
DOI: 10.3389/fpsyg.2021.624008
|View full text |Cite
|
Sign up to set email alerts
|

Training Executive Functions to Improve Academic Achievement: Tackling Avenues to Far Transfer

Abstract: The aim of training executive functions is usually to improve the ability to attain real-life goals such as academic achievement, that is, far transfer. Although many executive function trainings are successful in improving executive functions, far transfer is more difficult to achieve (cf. Diamond and Lee, 2011; Sala and Gobet, 2020). In this perspective article, we focus on the transfer of executive function training to academic performance. First, we disentangle possible sources of transfer problems. We arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 65 publications
0
14
0
1
Order By: Relevance
“…Efforts to develop training programs are progressing steadily in both lines of research and could be further stimulated by an orientation toward an integrated model of self‐regulation. The problem of far transfer of EF training remains a problem not finally solved (e.g., Gunzenhauser & Nückles, 2021). Far transfer describes that training EF leads to improvements in academic performance or general cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to develop training programs are progressing steadily in both lines of research and could be further stimulated by an orientation toward an integrated model of self‐regulation. The problem of far transfer of EF training remains a problem not finally solved (e.g., Gunzenhauser & Nückles, 2021). Far transfer describes that training EF leads to improvements in academic performance or general cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Our study extends this perspective by suggesting that it is not the tool itself, test vs observational questionnaire, but rather the context in which the child is observed that matters. The results of the mediation analysis conducted in our study show, indeed, that the "learning-related behaviors" way by which EFs support academic skills [68] can be measured by the observation of the self-regulatory behavior held by the child in a structured context, such as the assessment by EF tests. Observing the child's behavior, when carrying out particular activities during the administration of tests, can provide useful information on the child's learning behavior at school and on the effect of EFs on it.…”
Section: Discussionmentioning
confidence: 55%
“…At the cognitive level, the abilities to control impulsive behavior and interference stimuli, to upload information held in short-term memory and to change strategies or responses, represent mental operations needed in the first phases of alphabetization, when literacy and math are not automatized at all, nor they may rely on intuitive acquisition strategies [45,53]. Furthermore, as Gunzenhauser and Nuckles, [68] have suggested, EFs can support academic skills by a "learning-related behaviors" way, that is by supporting behaviors that are appropriate to the school context, such as maintaining attention in the classroom, resisting distractions, finishing activities, following the rules of the task. The "learning-related behaviors" are indeed self-regulatory behaviors within the school context.…”
Section: Executive Functions and Academic Learningsmentioning
confidence: 99%
“…Unfortunately, many existing interventions regarding the executive functions of children with ASD have shown little to no evidence of generalized benefits, especially referring to interference control [ 58 , 99 , 105 , 106 ]. To understand how and under what conditions the medium- and long-term transfer of learning could occur is still a challenge, with important practical implications that necessitate further research [ 91 , 107 ].…”
Section: Discussionmentioning
confidence: 99%